Improving your storytelling beyond the basics for all who tell stories in work or play - Lipman, Doug. (Little Rock August House, 1999)
The first steps in storytelling are often easy, because we tell stories informally every day. Once you take storytelling into the more formal contexts of performance or occupational uses, however, you may be faced with challenges you hadn't anticipated. You need information that goes beyond the basics. And you need it in a form that does not just tell you what to do but helps you make your own informed decisions.
Includes bibliographical references (p. [213]-219).
Keywords: Storytelling